Penelusuran Minat dan Bakat Olahraga pada Siswa Sekolah Menengah Pertama di Kabupaten Semarang Tahun Pelajaran 2019/2020 (Indonesian Journal for Physical Education and Sport, 2021)
Most junior high school students in Semarang Regency have a variety of sports talents, but some of the potential is not in accordance with the interests of students. The unknown sporting talents of students, the suitability of student interests and talents, the lack of knowledge of physical education teachers about scouting for sports search talent methods, and coaching that is not yet optimal. The purpose of this research is to determine the sports talent of junior high school students in Semarang Regency in the academic year 2019/2020 and the suitability of students interests. This research approach uses quantitative descriptive methods. The technique of collecting data uses The sport search talent test is used to find out the talents students have. The population in this study were junior high school students in Kendal Regency. The sampling technique uses purposive sampling. Data analysis in this research uses descriptive presents. Data processing using the sport search software application. The results of data analysis, a total of 20 students 13,1% of test takers had an interest in accordance with their talents and 133 students or 86,9% of test takers had an interest that was not in accordance with their talents. The conclusion obtained is that junior high school students in Semarang Regency have a variety of sports talents, but some of the potential is not in accordance with the interests of students. The suggestion from researchers is that the scouting and fostering talent process should be further improved to optimize student achievement. With this research, it is hoped that it will become a reference or alternative for the process of scouting and developing sports talent in Semarang Regency and other areas.